PROBLEMATIKA PENEGAKAN INSIDER TRADING DALAM PRAKTIK PASAR MODAL DI INDONESIA - Thorik, Achmad; Yulviani, Dian; Aji Pangestu, Ilham; Rizqi Fadhlillah, Muhammad (SUPREMASI HUKUM, 2024)
This research aims to identify and analyze the problems of insider trading in capital market practices in Indonesia. This research is normative legal research. Legal materials consist of primary and secondary legal materials obtained through literature study. The approach used includes a statutory regulatory approach. Based on the results of the discussion, it is known that first, Law Number 8 of 1995 concerning Capital Markets (UUPM) still has several weaknesses. Article 95 does not explain who is meant as an employee of the issuer. Apart from that, UUPM has a legal loophole to reach insider trading which is based on misuse of information to carry out transactions. UUPM only regulates insider trading that occurs as a result of violations of obligations. Second, the law enforcement process for insider trading violators in Indonesia is still considered very weak. Third, POJK Disgorgement is one of the government's efforts to deal with insider trading. These efforts include examination, investigation, evidence, dispute resolution, and imposition of sanctions. Researchers provide suggestions including, first, strengthening the role of OJK in terms of supervision. Second, the formation of a special unit consisting of several institutions to handle and resolve insider trading practices so that they are effective and efficient. Third, increasing understanding and education related to POJK Disgorgement in the community. Keywords: Problems; Insider Trading; Capital Market